Alteraciones auditivas en trabajadores expuestos al ruido industrial de la empresa IDUACERO CIA LTDA - Gabriela Katerine, Erazo Nogales (2022)
SUMMARY The present research work consisted of carrying out a bibliographic review,focused on determining the auditory alterations that occur in theworkers exposed to industrial noise in order to propose strategies that to improve the hearing condition in this working population. That is how,Taking this into account, the research problem was established in the first place,where they make known why noise is a risk factor that greatly affectsmeasure to workers in this important sector. The objectives were established to identify the main sourcesgenerators of noise in the company and the measures implemented for itsmitigation, describe the main hearing alterations that occur in th workers exposed to high levels of noise in Induacero and propose strategies for the prevention of hearing alterations in workers exposed to hignoise levels, using a mixed approach descriptive research. The objective of the research is to analyze the incidence of occupational noise in the workers of the company INDUACERO CIA. LTDA, throughevaluations, measurements, and calculations that allow determining the alterationhearing caused by industrial noise. The methodology was established in accordance with the regulations in force within the country and international standards to determine noise levels in the work area and the auditory alterations that occur in the workers of the company with the in order to increase their productivity and improve their health.xi The results obtained show that there are several sources of noise in the company,that exceed the most permissible limits. This produces a variety of symptoms an pain, which in the medium and long term can become alterations and damagirreparable, not only affecting the ear, but also other organs of the body,including the way of life of the affected person. With the analysis of the data, mitigation strategies have been established for the prevention of hearing alterations in workers exposed to high levels excessive noise within the company. Keywords: Noise level, exposure, health, alterations, audiograms, control regulations, hearing diseases